Measurement of dynamic forces experienced by an asymmetric yacht during a gybe, for use within sail simulation software - Banks, J.; Webb, A.; Spenkuch, T.; Turnock, S. R. (Procedia Engineering, 2010)
Assessing the relative performance and appropriate race tactics of competitive yacht designs led to the development of a fleet sail racing simulation tool - Robo-Race. Dynamic wind tunnel tests of a scale model asymmetric spinnaker passing through a constant wind speed to determine heel and drive forces have been carried out. The results of this have been used to propose a new model that significantly improves the physical fidelity of the gybe manoeuvre within Robo-Race.